BPI-ANCA is expressed in the airways of cystic fibrosis patients and correlates to platelet numbers and Pseudomonas aeruginosa colonization. (August 2020) - Hovold, Gisela; Lindberg, Ulrika; Ljungberg, Johanna K.; Shannon, Oonagh; Påhlman, Lisa I.
Abstract: Background: Autoantibodies to bactericidal/permeability-increasing protein (BPI), BPI-ANCA, are often present in serum of patients with cystic fibrosis (CF), and correlate to airway colonization with Pseudomonas aeruginosa . The aim of the study was to investigate if BPI-ANCA IgA is also present in the airways of CF patients, and if its presence correlates with neutrophil counts, platelets, and P. aeruginosa DNA in sputum. Methods: BPI-ANCA IgA was quantified in serum and sputum samples from adult CF patients (n = 45) by ELISA. Sputum neutrophil counts, platelets, and platelet-neutrophil complexes were assessed by flow cytometry, and P. aeruginosa DNA was analysed with RT-PCR. Results: Serum BPI-ANCA IgA was present in 44% of the study participants, and this group also had significantly enhanced BPI-ANCA levels in sputum compared to serum negative patients. Sputum levels of BPI-ANCA IgA correlated with P. aeruginosa DNA (r = 0.63, p = 0.0003) and platelet counts in sputum (r = 0.60, p = 0.0002). Conclusions: BPI-ANCA is expressed in the airways of CF patients and correlates with P. aeruginosa load and platelet counts, suggesting a link to airway inflammation and mucosal immunity. Highlights: BPI-ANCA is often present in serum of cystic fibrosis (CF) patients. Elevated serum BPI-ANCA titres are associated with poor prognosis. BPI-ANCA IgA is expressed in CF sputum and correlates with serum levels. Sputum BPI-ANCA correlates with P. aeruginosa load and platelet counts in sputum.